Kemampuan Reproduksi Induk dan Pertumbuhan Anak Kambing Peranakan Etawah, Gembrong, dan Kosta - A. Destomo; M. Syawal; A. Batubara (State Islamic University of Sultan Syarif Kasim Riau, 2020)
Indonesia has various types of local goat germplasm like a goat Peranakan Etawah (PE), Gembrong, and Kosta. Information of those local goats including the parent reproduction and kids productivity are still limited. Study aims to evaluate maternal reproduction capability and kids productivity of goat PE, Gembrong, and Kosta. Study was conducted in 24 does and 44 kids of PE, Gembrong, and Kosta in Loka Kambing Potong (Goat Research Station), Sumatera Utara. A goat mated with of the study from each the goat breed. Data of reproduction were collected from mating to calving. Data of kids productivity were collected from birth to nine month-old. As reproductive capability data, the highest litter size and type of birth were demonstrated in goat PE. Goat gembrong produced more male, whereas goat Kosta had shorter pregnant duration than other goats. Birth weight of PE was significantly different (p<0,05) to Gembrong and Kosta. Weaning weight was different (p<0,05) between PE and Kosta goat. In addition, daily gain of 6-months, 9-months weight, pre-weaning and postweaning showed no significant differences (P>0.05). Pre-weaning and post-weaning mortality was highest in Kosta.